2017
DOI: 10.18203/2320-6012.ijrms20173582
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Elaeocarpus floribundus fruit extracts for bioactive phytocomponents and antibacterial activity against food-borne bacteria

Abstract: Background: Medicinal plants possess several active components having antimicrobial activity. This study was undertaken to explore the antibacterial activity of Indian olive, Elaeocarpus floribundus, fruit extracts against potential food-borne bacterial isolates.Methods: The ethanolic extracts of olive seed (OSE) and mesocarp-epicarp (OMeE), and the aqueous extracts of olive seed (AqOSE) and mesocarp-epicarp (AqOMeE) were prepared, and analysed qualitatively for phytochemicals. The antibacterial activity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…floribundus fruit were prepared according to the method mentioned earlier [7], and tested against MRSA by agar well diffusion method [1] using nutrient agar medium (Hi-Media, India). The ZDI (nearest whole) on the test agar plate, around each of the wells, due to the antimicrobial action of the extracts at various concentrations (2.49, 4.15 and 8.3 mg/well), was measured and interpreted following the criteria mentioned earlier [1].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…floribundus fruit were prepared according to the method mentioned earlier [7], and tested against MRSA by agar well diffusion method [1] using nutrient agar medium (Hi-Media, India). The ZDI (nearest whole) on the test agar plate, around each of the wells, due to the antimicrobial action of the extracts at various concentrations (2.49, 4.15 and 8.3 mg/well), was measured and interpreted following the criteria mentioned earlier [1].…”
Section: Methodsmentioning
confidence: 99%
“…The olive extracts are natural sources of reducing as well as stabilizing agents for the synthesis of silver nanoparticles with antibacterial activity against spoilage and pathogenic bacteria, such as Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa [6]. It has been reported that the ethanolic as well as aqueous extracts of seed and mesocarp-epicarp of olive (E. floribundus) fruits had growth inhibitory activity against food-borne bacteria [7]. However, no scientific report has been made on anti-methicillin resistant …”
Section: Introductionmentioning
confidence: 99%
“…The plants were washed repeatedly, cut into pieces and dried under shade for two weeks. The dried plant materials were milled to form fine powder, and were processed to prepare the aqueous extract of E. fluctuans (AEE) and methanolic extract of E. fluctuans (MEE), as described earlier [6,7]. For the preparation of MEE, 5 g of sample powder was soaked in 50 ml methanol for 72 h with manual shaking at 2 h intervals, and in order to prepare AEE, 5 g of the powdered E. fluctuans was boiled in a conical flask containing 50 ml double distilled water, for 30 min, without pressure.…”
Section: Plant Materials and Extract Preparationmentioning
confidence: 99%
“…The bioactive components, such as flavonoids, steroids, terpenoids, quinone, phenol, cardiac glycosides, anthraquinone glycosides and saponins, present in the plant extracts have been detected qualitatively, following the protocol mentioned elsewhere [6,8].…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…The seeds and mesocarp-epicarp parts of the fruits were separated, sheddried, and thereafter (mesocarp-epicarp parts and seeds) were grinded. The ethanolic extracts of the grinded materials (25 g in 200 ml) were prepared as described earlier 29,30 . The olive seed ethanolic extract (OSE; 125 μg/μl)) as well as the olive mesocarp-epicarp ethanolic extract (OME; 125 μg/μl), after filtration, were stored at 4⁰C, for further work.…”
Section: Preparation Of Plant Extractsmentioning
confidence: 99%